Global Spectral Properties and Lithology of Mercury: The Example of the Shakespeare (H‐03) Quadrangle. Issue 9 (2nd September 2019) - Bott, N.; Doressoundiram, A.; Zambon, F.; Carli, C.; Guzzetta, L.; Perna, D.; Capaccioni, F.
Abstract: The MErcury Surface, Space ENvironment, GEochemistry and Ranging mission showed the surface of Mercury with an accuracy never reached before. The morphological and spectral analyses performed thanks to the data collected between 2008 and 2015 revealed that the Mercurian surface differs from the surface of the Moon, although they look visually very similar. The surface of Mercury is characterized by a high morphological and spectral variability, suggesting that its stratigraphy is also heterogeneous. Here, we focused on the Shakespeare (H‐03) quadrangle, which is located in the northern hemisphere of Mercury. We produced an 8‐color cube of this quadrangle at 450‐m per pixel spatial resolution and with a complete coverage. Various selected color maps based on this eight‐color cube were used to analyze the spectral properties of this region to define its compositional variability and identify some clear units constrained by relevant spectral parameters: for example, we identified a higher concentration of low reflectance material around three main craters of Shakespeare (Degas, Akutagawa, and Sholem Aleichem) and in the area to the south of Sobkou Planitia delimited by 24.4°N to 28.4°N and −140°W to −125°W. Moreover, we selected some regions of interest, which can be proposed as particularly interesting targets for the Visual and Infrared Hyper‐spectral Imager and Mercury Radiometer and Thermal Imaging Spectrometer instruments onboard the BepiColombo spacecraft. This work can help for the geological analysis of this quadrangle, by integrating information that are usually not derived with a single morphostratigraphic analysis. Key Points: We used the MDIS‐WAC data to produce an eight‐color mosaic of the Shakespeare quadrangle We identified spectral units from the maps of Shakespeare We selected two regions of high interest as potential targets for the BepiColombo mission Plain Language Summary: The MErcury Surface, Space ENvironment, GEochemistry and Ranging mission showed Mercury's surface with an accuracy never reached before . The analyses performed thanks to the data collected between 2008 and 2015 revealed that the Mercurian surface differs from the surface of the Moon, although they look visually very similar. Mercury's surface is characterized by a high variability in terms of shape and colors, suggesting that its subsurface is also heterogeneous. Here, we focused on the region called Shakespeare, which is located in the north hemisphere of Mercury. We produced a mosaic of images of this region for several colors at high resolution and with a complete coverage. Various selected color maps based on this mosaic were used to analyze the properties of this area to define its compositional variability: for example, we identified a higher concentration of dark material around three craters of Shakespeare (Degas, Akutagawa, and Sholem Aleichem) and in the south of the Sobkou basin. Moreover, we selected some interesting regions that can be proposed as particularly interesting targets for instruments onboard the BepiColombo spacecraft. This work can help for the geological analysis of this quadrangle, by adding information that are usually not derived with a single analysis of landforms.